Effects of soil enrichment, watering and seedling age on establishment of Mediterranean woody species - Siles, Gemma; Rey, Pedro J; Alcántara, Julio M; Bastida, Jesús M; Herreros, Jose L (Acta Oecologica, 2010)
Vegetation restoration in strongly degraded lands has inherent limitations. Among the most relevant limitations in Mediterranean Mountains are severe drought and stressful levels of irradiance during summer. Thus, it is common that seedlings planted in open ground incur high rates of early mortality. In the context of a project of restoration of a burned area in Southern Spain, we evaluate the efﬁciency of watering and enrichment with native soil, and the inﬂuence of seedling age on survival and growth of 9 late-successional tall shrubs and trees planted in open ground. We also explore how small-scale variation in environmental variables relates to establishment success. Our results show an overall positive effect of watering on the survival of planted seedlings, while the effects of enrichment with native soil and age of planted seedlings were species-speciﬁc. Seedling establishment varied markedly with the presence of ravines, which duplicated seedling survival. This suggests that ravines may be more easily restored, improving their role as corridors in landscape designs of restoration. Independently of the treatment applied, Rosa sp. and Crataegus monogyna, both ﬂeshy-fruited species, had the highest rates of establishment. In conclusion, this study shows the viability of low aggressive restoration techniques to assist vegetation recovery in ﬁre-degraded environments. Speciﬁcally, watering and planting in ravines should be considered where restoration practices are applied in areas lacking vegetation cover. Some species highly attractive for animal dispersers and of easy establishment (Rosa sp. and Crataegus sp.) could be used to enhance spontaneous regeneration within and beyond corridors through increasing seed attraction and dissemination.
Keywords: Enrichment with native soil; irrigation; Mediterranean vegetation; Post-ﬁre restoration; seedling survival

Influence of Quercus ilex trees on herbaceous production and nutrient concentrations in southern Portugal - Cubera, Elena; Manuel Nunes, Jorge; Madeira, Manuel; Gazarini, Luíz (Journal of Plant Nutrition and Soil Science, 2009)
In an open woodland in Portugal, the nature of interactions between Quercus ilex trees and herbaceous plants was assessed during 2 years by studying how manipulation of incident solar radiation, water and nutrient supply affect the herbaceous biomass and N, K, P, Ca, Mg, and Mn concentrations. Measurements were carried out in three environments consisting of (1) open grassland, (2) beneath the tree canopy, and (3) under artificial shade. Each of these environments was subjected to two regimes of fertilization and two water levels in a factorial design. The fertilizer treatment consisted of application of no fertilizer or a combination of 200 kg calcium ammonium nitrate ha–1 (26% N) and 350 kg superphosphate ha–1 (8% P), while the water-supply treatment consisted of either no irrigation or irrigation fortnightly from February 1 to April 30. Grasses showed significantly lower nutrient concentrations than forbs. However, nutrient concentrations of the whole herbaceous community were within the recommended ranges for cattle nutrition. A negative effect of shade on herbaceous biomass production was observed. The effect of watering on herbaceous biomass was less prominent than the effect of fertilization, irrespective of the environment, suggesting that Q. ilex does not compete for soil-water resources with herbaceous biomass in this ecosystem. Fertilization increased total biomass by 106%, 49%, and 97% in the open grassland, beneath the tree canopy, and under artificial shade, respectively. During the first and second year, fertilization increased herbaceous P concentrations by 24% and 83%, respectively, if compared with concentrations obtained at the unfertilized plots. Higher K and Mg concentrations were observed in herbaceous plants beneath the tree canopy than in the open areas, indicating a positive effect of trees on pasture quality. The positive and negative effects of trees on understory forage are discussed.
Keywords: fertilization; herbaceous biomass; irrigation; shade

Influence of Quercus ilex trees on herbaceous production and nutrient concentrations in southern Portugal - Cubera, Elena; Manuel Nunes, Jorge; Madeira, Manuel; Gazarini, Luíz (Journal of Plant Nutrition and Soil Science, 2009)
In an open woodland in Portugal, the nature of interactions between Quercus ilex trees and herbaceous plants was assessed during 2 years by studying how manipulation of incident solar radiation, water and nutrient supply affect the herbaceous biomass and N, K, P, Ca, Mg, and Mn concentrations. Measurements were carried out in three environments consisting of (1) open grassland, (2) beneath the tree canopy, and (3) under artificial shade. Each of these environments was subjected to two regimes of fertilization and two water levels in a factorial design. The fertilizer treatment consisted of application of no fertilizer or a combination of 200 kg calcium ammonium nitrate ha–1 (26% N) and 350 kg superphosphate ha–1 (8% P), while the water-supply treatment consisted of either no irrigation or irrigation fortnightly from February 1 to April 30. Grasses showed significantly lower nutrient concentrations than forbs. However, nutrient concentrations of the whole herbaceous community were within the recommended ranges for cattle nutrition. A negative effect of shade on herbaceous biomass production was observed. The effect of watering on herbaceous biomass was less prominent than the effect of fertilization, irrespective of the environment, suggesting that Q. ilex does not compete for soil-water resources with herbaceous biomass in this ecosystem. Fertilization increased total biomass by 106%, 49%, and 97% in the open grassland, beneath the tree canopy, and under artificial shade, respectively. During the first and second year, fertilization increased herbaceous P concentrations by 24% and 83%, respectively, if compared with concentrations obtained at the unfertilized plots. Higher K and Mg concentrations were observed in herbaceous plants beneath the tree canopy than in the open areas, indicating a positive effect of trees on pasture quality. The positive and negative effects of trees on understory forage are discussed.
Keywords: fertilization; herbaceous biomass; irrigation; shade

Growth and survival in Quercus ilex L. seedlings after irrigation and artificial shading on Mediterranean set-aside agricultural land - Rey Benayas, José M. (Ann. For. Sci., 1998)
Considerable quantities of agricultural land are being transformed into forested lands in E.U. countries. To assess afforestation practice, we analyzed the growth and survival of 800 Quercus ilex sp. ballota seedlings in set-aside agricultural land under semi-arid Mediterranean climate conditions in central Spain. The survival and growth of the seedlings were monitored for 3 years after planting with an experimental design that included all four combinations of: i) irrigation or no irrigation during the dry season; and ii) artificial shading or no shading. Significant differences in survival and growth (height, stem diameter and crown projected area) were found among treatments. Survival was lowest (53 %) in the control plots, and very similar (around 93 %) for the irrigation, shade and combined treatments. Most of the mortality occurred after the first dry season. The high survival rate in irrigated but not shaded plots coincided with a thick layer of the weed Amaranthus retroflexus L. (in the first dry season). Seedling growth was greatest on average under irrigation and shade conditions. Shade was found to have a significant effect for all growth measurements, while irrigation alone only affected stem diameter growth and crown projected area in interaction with shade. Growth measurements were correlated to microclimatic conditions in the plots as measured by the amounts of water and actual evapotranspiration. We conclude that the attenuation of summer stress must be considered in the early stages of successful plantation practice of set-aside agricultural land in a dry environment.
Keywords: Agricultural land; Growth; irrigation; shade; Survival

Growth and survival in Quercus ilex L. seedlings after irrigation and artificial shading on Mediterranean set-aside agricultural land - Rey Benayas, José M (Ann. For. Sci., 1998)
Considerable quantities of agricultural land are being transformed into forested lands in E.U. countries. To assess afforestation practice, we analyzed the growth and survival of 800 Quercus ilex sp. ballota seedlings in set-aside agricultural land under semi-arid Mediterranean climate conditions in central Spain. The survival and growth of the seedlings were monitored for 3 years after planting with an experimental design that included all four combinations of: i) irrigation or no irrigation during the dry season; and ii) artificial shading or no shading. Significant differences in survival and growth (height, stem diameter and crown projected area) were found among treatments. Survival was lowest (53 %) in the control plots, and very similar (around 93 %) for the irrigation, shade and combined treatments. Most of the mortality occurred after the first dry season. The high survival rate in irrigated but not shaded plots coincided with a thick layer of the weed Amaranthus retroflexus L. (in the first dry season). Seedling growth was greatest on average under irrigation and shade conditions. Shade was found to have a significant effect for all growth measurements, while irrigation alone only affected stem diameter growth and crown projected area in interaction with shade. Growth measurements were correlated to microclimatic conditions in the plots as measured by the amounts of water and actual evapotranspiration. We conclude that the attenuation of summer stress must be considered in the early stages of successful plantation practice of set-aside agricultural land in a dry environment.
Keywords: Agricultural land; Growth; irrigation; shade; Survival

Influencia del tamaño de bellota y del régimen de riego en la calidad de planta de alcornoque cultivada en vivero - Pardos Mínguez, M; Cañellas, I; Bachiller, A (II Congreso Forestal Español, 1997)
The effect of three acorn sizes (small, medium and large, 2.5, 5 and 8.8 g mean fresh weight, respectively) and two irrigation regimes (Rl=2R2) in the growth of cork oak containerized (Forest Pot 300) seedlings was studied. The seedlings were grown in the nursery for one year.The results showed the influence of the acorn size on caliper, root volume, shoot, root and acorn dry weights, leaf area, leaf weight ratio (L WR), leaf area ratio (LAR), midday water potential and transpiration. Irrigation was statistically significant for height and totalleaf area. Water potential reached less than -2 MPa in July. This fact reveals the adaptation of the species to drought.
Keywords: acorn size; irrigation; Quercus suber; seedling quality

Influencia del tamaño de bellota y del régimen de riego en la calidad de planta de alcornoque cultivada en vivero - Pardos Mínguez, M.; Cañellas, I.; Bachiller, A. (II Congreso Forestal Español, 1997)
The effect of three acorn sizes (small, medium and large, 2.5, 5 and 8.8 g mean fresh weight, respectively) and two irrigation regimes (Rl=2R2) in the growth of cork oak containerized (Forest Pot 300) seedlings was studied. The seedlings were grown in the nursery for one year.The results showed the influence of the acorn size on caliper, root volume, shoot, root and acorn dry weights, leaf area, leaf weight ratio (L WR), leaf area ratio (LAR), midday water potential and transpiration. Irrigation was statistically significant for height and totalleaf area. Water potential reached less than -2 MPa in July. This fact reveals the adaptation of the species to drought.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español
Keywords: acorn size; irrigation; Quercus suber; seedling quality

Mortalidad y crecimiento de plantones de quercus ilex en una tierra agrícola abandonada en toledo - Rey Benayas, Jose Maria (II Congreso Forestal Español, 1997)
Considerable quantities of agricultural land are being transformed into forested lands in E.U. countries. To assess afforestation practice, we analyzed the growth and mortality of 800 Quercus ilex' subsp. ball()ta seedlings in a set-aside agricultural land under semi-arid Mediterranean climate conditions in Toledo, Spain. The mortality and growth of the seedlings were monitored for three years after planting with an experimental design that included all four combinations of i) irrigation or no irrigation in the dry season and ii) artificial shading or no shading. Significant differences in mortality and growth (height, stem diameter and crown projected area) were found among treatments. Mortality was highest (47%) in the control plots, and very similar (around 7%) for the irrigation, shade, and combined treatments. Most of the mortality occurred after the first dry season. The low mortality in irrigated but not shaded plots in the first dry season is attributed to the protective role of a thick layer of the weed Amaranthus retroflexus L. Seedling growth was greatest on average under irrigation and shade conditions. Shade was found to have a significant effect for all growth measurements, while irrigation alone only affected stem diameter growth, and crown projected area in interaction with shade. We conclude that the reduction of summer stress must be considered in the early stages for successfull afforestation practices with oaks in set-aside agricultural lands of dry environments.
Keywords: Agriculturalland; Growth; irrigation; shade; Survival

Canopy nutrient content of a Quercus ilex L. forest: fertilization and irrigation effects - SABATE, Santiago; Gracia, Carlos a; Ecology, Forest; Barcelona, Universitat De (Forest Ecology and Management, 1994)
A multifactorial ANOVA experiment was designed for a Quercus ilex L. forest at the Prades Experimental Complex of Catchments in Tarragona (northeast Spain). The purpose of this study was to clarify the relative importance of water, nitrogen and phosphorus as factors controlling primary production. Eight plots comprising all possible combinations of the three factors (including a control) were laid out in three replicate blocks. Fertilizers were applied in March 1989 (125 kg ha−1 P, 250 kg ha−1 N). Irrigation was applied at a rate of 20 mm week−1 during the warm season. Nitrogen and phosphorus contents and their distribution in leaves and stems as a response to the experiment are presented in this paper. These variables as well as the structural characteristics were selected because they are among the most dynamic and should present changes over short time periods following changes in environmental conditions. The values before initial treatments (autumn 1988) and after treatments (summer 1990) were analysed. Results showed that water treatments affect the nutrient content; the lower concentrations found in water treatments may probably be explained as a dilution effect after an increase of production. Nitrogen treatments significantly increase the nitrogen concentration in young leaves while phosphorus treatments do not have significant effect on the phosphorus concentrations. Nevertheless, phosphorus treatment significantly lowers the potassium concentration.
Keywords: Canopy; fertilization; irrigation; nutrient content; Quercus ilex

Effects of irrigation and fertilization on stem diameter growth in a Mediterranean holm oak forest - Mayor, Xavier; Rodà, Ferran (Forest Ecology and Management, 1994)
The effects of irrigation and fertilization on stem diameter growth are reported for holm oak (Quercus ilex L.), an evergreen tree that is a common dominant in Mediterranean forests. The experiment was conducted at Prades (northeastern Spain) in a holm oak stand with a high density of stems of resprout origin (x = 18275 stems ha−1), a widespread stand structure in the abandoned coppices that cover extensive tracts of Mediterranean mountains. Mean annual rainfall is 580 mm. Eight treatments were used in each of three blocks, resulting from the factorial combination of: (i) irrigation at rates of about 20 mm week−1 during three consecutive warm seasons; (ii) nitrogen fertilization in a single application of 250 kg N ha−1; (iii) phosphorus fertilization in a single application of 125 kg P ha−1. Stem diameters at 50 cm from the ground were measured before and 3 years after treatment application began. Stem diameter increments in control plots were very low (x ± SE 0.27 ± 0.07 mm year−1), probably as a result of the high stand density and low water availability. Stem diameter growth was positively but loosely correlated with initial stem diameter. Irrigation significantly (P < 0.01) increased mean stem diameter growth by 66%, but N and P fertilization did not. Surprisingly, there were no significant interactions between irrigation and fertilization, i.e. irrigated and fertilized trees did not grow significantly faster than irrigated-only trees. Effects of irrigation were larger on plots having lower initial basal area of holm oak. Irrigation increased stem diameter growth more in large trees than in smaller ones, thus enhancing the pre-existent inequalities in growth rates. Stem diameter growth in this high density stand is limited by water availability but has not responded to N or P additions during the first 3 years after fertilization.
Keywords: fertilization; Growth; irrigation; Quercus ilex; Stem diameter growth

EFFECTS OF IRRIGATION AND FERTILIZATION ON STEM DIAMETER GROWTH IN A MEDITERRANEAN HELM OAK FOREST - Mayor, X; Rodà, F (FOREST ECOLOGY AND MANAGEMENT, 1994)
The effects of irrigation and fertilization on stem diameter growth are reported for helm oak (Quercus ilex L.), an evergreen tree that is a common dominant in Mediterranean forests. The experiment was conducted at Prades (northeastern Spain) in a helm oak stand with a high density of stems of resprout origin (($) over bar x = 18275 stems ha(-1)), a widespread stand structure in the abandoned coppices that cover extensive tracts of Mediterranean mountains. Mean annual rainfall is 580 mm. Eight treatments were used in each of three blocks, resulting from the factorial combination of: (i) irrigation at rates of about 20 mm week(-1) during three consecutive warm seasons; (ii) nitrogen fertilization in a single application of 250 kg N ha(-1); (iii) phosphorus fertilization in a single application of 125 kg P ha(-1). Stem diameters at 50 cm from the ground were measured before and 3 years after treatment application began. Stem diameter increments in control plots were very low (($) over bar x+/-SE 0.27+/-0.07 mm year(-1)), probably as a result of the high stand density and low water availability. Stem diameter growth was positively but loosely correlated with initial stem diameter. Irrigation significantly (P<0.01) increased mean stem diameter growth by 66%, but N and P fertilization did not. Surprisingly, there were no significant interactions between irrigation and fertilization, i.e. irrigated and fertilized trees did not grow significantly faster than irrigated-only trees. Effects of irrigation were larger on plots having lower initial basal area of helm oak. Irrigation increased stem diameter growth more in large trees than in smaller ones, thus enhancing the pre-existent inequalities in growth rates. Stem diameter growth in this high density stand is limited by water availability but has not responded to N or P additions during the first 3 years after fertilization.
Keywords: fertilization; Growth; irrigation; Stem diameter growth